Issues for Development of Economic System for Subsurface Resource Management in Russia through Lens of Economic Process Servitization - Vasilenko, Natalia; Khaykin, Marck; Kirsanova, Natalia; Lapinskas, Arunas; Makhova, Larisa (International Journal of Energy Economics and Policy, 2019)
The article dwells upon the main economic issues and development of subsurface resource management in the national economy. The question of servitization of subsurface resource management is discussed for the first time. The article focuses on the following issues: the mine rent, the necessity to restructure property in subsurface resource management considering corporate relations; managing the system for economic interests of subsurface resource users, the state, and society; optimizing the payment and taxation systems for use of subsurface resources. Keywords: economy servitization, use of subsurface resources, system of payments for natural resources JEL Classifications: H30, L89, O13 DOI: https://doi.org/10.32479/ijeep.8303